Occupational Health and Safety (OHS) Impact on Time and Cost of East Java'S National Road Projects - Nainggolan, Boyke Mangaratua; Beatrix, Michella (Indonesian Journal Of Civil Engineering Education, 2023)
Road infrastructure development has increased in the last three years. Like the construction of other infrastructure projects, the implementation of this road project also carries a high risk of work accidents. Therefore, knowledge of Occupational Safety and Health (OHS) is needed to minimize the potential risk of work accidents. The purpose of this study is to determine the implementation of Occupational Safety and Health (OHS) in national road projects in East Java and review what can be done so that the implementation of Occupational Safety and Health (OHS) in national road projects in East Java can run better. This research began with data collection through the questionnaire method, distributed to the national road project head office in East Java, with the respondents being project managers or project leaders. Furthermore, the collected questionnaire data were analyzed using the Partial Least Square (PLS) method. The results of the partial least squares analysis show that the factor that most influences the application of OHS is the Management Role Factor (X2) which ranks first, with the Management Role variable having an effect of 25.07%.